The Role of Transformational Leadership on School Achievement - Masaong, Abdul Kadim; Arifin; Dewi Purnama Hamid (Universitas Pendidikan Ganesha, 2023)
The education system in Indonesia is still in the fifth lowest position in the education index of ASEAN countries. Therefore, the government must take transformative steps to improve the Indonesian education system. This study examines the transformation of cultural values and their influence on achievement. This type of research is qualitative. The method used is a qualitative approach with a case study design. Data collection techniques are carried out through observation, interviews, and documentation. Data analysis is done by condensing, presenting, and drawing conclusions. The study results show that the cultural values that are transformed into the lives of school members are religious, social, cooperation, nationalism, and integrity values. These cultural values are transformed into non-verbal symbols by using the slogan 5S and caring for the environment and into verbal symbols by giving awards and praise for the performance of school members, conveying directly about the cultural values that are applied, giving encouragement and motivation to school members to have good ethics and morals, and giving encouragement to create a clean and healthy school atmosphere. The impact of the transformation of cultural values is to increase the motivation of school members to excel in academic and non-academic fields to create a superior generation with strong character and cultured with critical and analytical thinking.